Some stylized facts about international trade flows - Harris, Mark; Konya, L.; Matyas, L. (Wiley-Blackwell Publishing Ltd., 2012)
Since the mid-1990s there has been a proliferation of empirical models in the trade literature. Focus has ranged from the effect of particular explanatory variables to improved econometric techniques. However, there appears to be a lack of analyses on large international trade datasets aiming at describing the “stylized facts” of observed bilateral trade flows. Uncovering them is crucial as any empirical econometric model should reflect the basic properties of the data generating process. On the basis of a large panel dataset this paper finds that bilateral trade, despite being often unbalanced, tends to be reciprocal and persistent, and that the extensive margin of trade must not be disregarded. Moreover, bilateral trade flows are probably best modeled as a mixed panel of stationary and non-stationary processes. The stationary vs non-stationary separation of these flows, although not random, does not appear to be related to any common characteristics of the trading partners.